Revolt in the Middle East : Arab monarchies next? - Dorsey, James M. (2013)
The ever sharper sectarian divide between Sunni and Shiite Muslims in the Middle East consitutes the Achilles heel of gulf monarchies like Saudi Arabia and Bahrain. They have been resisting political reforms and seeking to insulate themselves from the wave of popular protests that have swept the region for the past two years.